THE EFFECTS OF COUNTRY OF ORIGIN AND PERCEIVED RISK ON INITIAL TRUST: AN EXPERIMENTAL EVALUATION OF THE PERCEPTION OF INDONESIAN CONSUMERS ON SERVICE INDUSTRY ACROSS HIGH RISK AND LOW RISK SERVICES - Tara Farina; Feranita Feranita (Journal of Business Strategy and Execution, 2010)
To uncover how COO and perceived risk affect the initial trust in service industry; and to compare these effects across two service industry – high risk versus low risk. A total of 180 respondents were evaluated with different combinations across 2 service industries. The research findings confirmed the effect of country of origin and corporate reputation on initial trust and the relationship between perceived risk and COO. Before engaging to a service, respondents put into considerations for COO and corporate reputation. COO effect may differ across different service industry.